Two conformational states of the membrane-associated Bacillus thuringiensis Cry4Ba δ-endotoxin complex revealed by electron crystallography: Implications for toxin-pore formation - Puey Ounjai (2018)
The insecticidal nature of Cry δ-endotoxins produced by Bacillus thuringiensis is generally believed to be caused by their ability to form lytic pores in the midgut cell membrane of susceptible insect larvae. Here we have analyzed membrane-associated structures of the 65-kDa dipteran-active Cry4Ba toxin by electron crystallography. The membrane-associated toxin complex was crystallized in the presence of DMPC via detergent dialysis. Depending upon the charge of the adsorbed surface, 2D crystals of the oligomeric toxin complex have been captured in two distinct conformations. The projection maps of those crystals have been generated at 17 Å resolution. Both complexes appeared to be trimeric; as in one crystal form, its projection structure revealed a symmetrical pinwheel-like shape with virtually no depression in the middle of the complex. The other form revealed a propeller-like conformation displaying an obvious hole in the center region, presumably representing the toxin-induced pore. These crystallographic data thus demonstrate for the first time that the 65-kDa activated Cry4Ba toxin in association with lipid membranes could exist in at least two different trimeric conformations, conceivably implying the closed and open states of the pore. © 2007 Elsevier Inc. All rights reserved.